Study the of effect of micro and nanoCadmium Oxide on the hardness test of (epoxy-polyurethane) blend - Suhail, Ghasaq Talal; Anter, Faik Hammad; Al-Sarraj, Ziyad Shihab (Iraqi Journal of Science, 2018)
This research includes using epoxy resin and polyurethane resin to form a blend (EP+PU) with different resin ratios (90 – 10)%, (80 – 20)%, (70 – 30)%, and (60 – 40)% to achieve best ratio for impact strength as a function of better toughness; then reinforced with micro and nano (CdO) with weight fraction (0.02, 0.04, 0.06, 0.08). Mechanical properties were studied including hardness before and after exposure to UV irradiation. Results showed that the composite (nano CdO+ blend) had better properties compared with (micro CdO+ blend) composite. Also hardness show increases with increasing the weight fraction for all samples.